Factors determining floristic composition and functional diversity of plant communities of Mount Oku forests, Cameroon - Marie Caroline Momo Solefack; Evariste Fongnzossie Fedoung; Lucie Félicité Temgoua (Journal of Asia-Pacific Biodiversity, 2018)
Mount Oku, in north-western Cameroon, holds many endemic and restricted-range species. This study identifies factors influencing the species and functional diversity of plant communities in Mount Oku forests. We specifically look at whether the altitudinal gradient, which classically structures the mountain vegetation, has shifted in response to the influence of human activities. To explore variations in the vegetation composition of the study area, we realized 102 floristic plots along an altitudinal gradient and environmental conditions records (abiotic and biotic variables, human proximity indexes, and land uses at certain periods). Plant species identified were also characterized by a series of life traits (biological type, type of diaspore, leaf size, phytogeography, dispersal pattern, and altitudinal distribution). Multivariate analyses (nonmetric multidimensional scaling and coinertia) have identified the main types of forest vegetation and link functional diversity to environmental factors. The results show that humans have altered the functional composition of vegetation by rearing domestic animals in the understorey forest near the summit. The results also show that it is sometimes difficult to separate the effect of the altitude from the effect of human presence on the plant composition. Greater efforts of biodiversity conservation in high species-rich areas in Mount Oku should be made.